2020
DOI: 10.3390/ijms21207437
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting SRC Kinase Signaling in Pancreatic Cancer Stem Cells

Abstract: The proto-oncogene nonreceptor tyrosine-protein kinase SRC is a member of the SRC family of tyrosine kinases (SFKs), and its activation and overexpression have been shown to play a protumorigenic role in multiple solid cancers, including pancreatic ductal adenocarcinoma (PDAC). PDAC is currently the seventh-leading cause of cancer-related death worldwide, and, by 2030, it is predicted to become the second-leading cause of cancer-related death in the United States. PDAC is characterized by its high lethality (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 95 publications
(149 reference statements)
1
13
0
Order By: Relevance
“…Increased activity of Src was reported to promote hyper-proliferation, migration, invasion and epithelial-to-mesenchymal transition during cancer progression (Guarino 2010 ). Src was over-expressed and activated in PDAC (Alcalá et al 2020 ), which promoted the metastasis of PDAC (Ogawa et al 2019 ). LY-1816, a Src inhibitor, has been demonstrated to have clinical therapeutic effect on PDAC (Yang et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased activity of Src was reported to promote hyper-proliferation, migration, invasion and epithelial-to-mesenchymal transition during cancer progression (Guarino 2010 ). Src was over-expressed and activated in PDAC (Alcalá et al 2020 ), which promoted the metastasis of PDAC (Ogawa et al 2019 ). LY-1816, a Src inhibitor, has been demonstrated to have clinical therapeutic effect on PDAC (Yang et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…PI3KR1 expression is associated with lymphangiogenesis, lymphatic metastasis, and survival in PC [ 101 , 102 ]. Src (encoded by SRC ) is an oncogenic kinase that regulates EMT, migration, invasion, cell adhesion and spreading, metastasis, stem-like features, proliferation, growth, angiogenesis, and survival of PC cells, and its expression and activity are further correlated with the survival, progression, and therapy response rate of patients with PC [ 103 114 ]. Signal transducer and activator of transcription (STAT)-3 (encoded by STAT3 ) induces initiation, progression, proliferation, metastasis, angiogenesis, EMT, self-renewal stemness, migration, invasion, immune escape, and resistance to anoikis, chemotherapy, and radiotherapy of PC cells, and its activation is associated with poor prognosis of patients with PC [ 115 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the inactivating mutation of the SH2 and SH3 domains R175 L and W118 A /R175 L significantly reduced BCSCs renewal in both cell lines, supporting the relevance of the adapter domains in the renewal of the tumor initiating cells. In primary PDAC cultures, established from patient-derived xenografts with Dasatinib or PP2 reduced the clonogenic, self-renewal, and tumor-initiating capacity of PaCSCs, which we attribute to the downregulation of key signaling factors such as p-FAK, p-ERK1-2, and p-AKT [ 51 ].…”
Section: Discussionmentioning
confidence: 99%